2011
DOI: 10.5194/acp-11-7893-2011
|View full text |Cite
|
Sign up to set email alerts
|

Carbonaceous species in PM<sub>2.5</sub> at a pair of rural/urban sites in Beijing, 2005–2008

Abstract: Abstract. One-week integrated PM 2.5 samples were collected over four years (2005)(2006)(2007)(2008) at a pair of sites, one rural and one urban site, in the area of Beijing, China. Weekly organic and elemental carbon (OC and EC) concentrations from these samples were measured to investigate their atmospheric concentrations, temporal variation patterns and the factors influencing these aspects. A slightly systematic decrease in annual mean concentration of OC and an opposite trend for EC at both sites was obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 41 publications
(43 reference statements)
2
29
1
Order By: Relevance
“…This is supported by the fact that the average Na + and Cl − ratio of 2.1 (ranging from 0.7 to 13) was much higher than the reported ratio of 1.16 from seawater (Moller, 1990). This is understandable since Beijing is about 160 km away from the Bohai Sea in the southeast and the wind from that direction in summer is usually mild (Yang et al, 2011a). Factor 2 has high loading for SO 2− 4 , NO − 3 , and NH + 4 , suggestive of the secondary pollution formed in the atmosphere from their precursors -SO 2 , NO x , and NH 3 .…”
Section: Chemical Composition and Sources Of Major Ionssupporting
confidence: 52%
See 2 more Smart Citations
“…This is supported by the fact that the average Na + and Cl − ratio of 2.1 (ranging from 0.7 to 13) was much higher than the reported ratio of 1.16 from seawater (Moller, 1990). This is understandable since Beijing is about 160 km away from the Bohai Sea in the southeast and the wind from that direction in summer is usually mild (Yang et al, 2011a). Factor 2 has high loading for SO 2− 4 , NO − 3 , and NH + 4 , suggestive of the secondary pollution formed in the atmosphere from their precursors -SO 2 , NO x , and NH 3 .…”
Section: Chemical Composition and Sources Of Major Ionssupporting
confidence: 52%
“…Lying in the north warm temperate zone, Beijing has typical continental monsoon climate with four distinct seasons. From November-April (dry months), the prevailing airflow from the northwest is dry and cold, while at other times the local winds are moderate and mostly from the south and southeast (Yang et al, 2011a (Fig. 1).…”
Section: Sampling Location and Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work (Chang et al, 2016) shows that the month of September in Shanghai has the highest planetary boundary layer (PBL), which favors the vertical dispersion of ground-emitted pollutants. Additionally, higher temperature in September could lead to a shift in the gas-particle equilibrium, with more semi-volatile organic compounds (SVOCs) remaining in the gas phase (Yang et al, 2011). In addition, carbonaceous aerosols can also be effectively removed by wet deposition attributed to large amount of precipitation in September .…”
Section: Monthly and Seasonal Variationsmentioning
confidence: 99%
“…Observational and modeling studies have reported high aerosol concentrations in the eastern United States (US) (Malm 2004;Park et al 2003Park et al , 2004Walker et al 2012), eastern China (Zhang et al 2012b;Wang et al 2013;Mu and Liao 2014), and Europe (Megaritis et al 2014;Andersson et al 2007) as a result of the large anthropogenic emissions of aerosols and aerosol precursors in these regions (Dutkiewicz et al 2000;Vestreng et al 2007;Hand et al 2012;Mijling et al 2013). Previous studies also showed that the interannual variations (IAVs) of aerosols were significant in the eastern US (Alston et al 2012), eastern China (Yang et al 2011;Mu and Liao 2014), and Europe (Andersson et al 2007). The IAVs in aerosol concentrations were found to be sensitive to the IAVs in anthropogenic emissions of aerosols and aerosol precursors (Mylona 1996;Irie 2005;Ohara et al 2007;Vestreng et al 2007;Xing et al 2013) and in meteorological conditions, since the meteorology modulates the processes of dilution, transport, deposition, and chemical reaction (Andersson et al 2007;Zhao et al 2012;Mu and Liao 2014).…”
Section: Introductionmentioning
confidence: 90%